Remediation of Pb (II), Cd (II), and Zn (II) from aqueous solutions using porous (styrene-divinylbenzene)/Cu-Ni bimetallic nanocomposite microspheres continuous fixed-bed column study - Thrikkykkal, Hridya (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
Bimetallic nanoparticles (BNPs) have been used as a new line of defence against heavy metal contamination among several types of nanoparticles (NPs) due to their enhanced, synergistic activity. In this study, we investigated the adsorption behaviour of porous (styrene-divinylbenzene)/CuNi bimetallic nanocomposite (P(St-DVB)/CuNi BNC) in a continuous flow fixed-bed column and its ability to remove Pb (II), Cd (II), and Zn (II) ions from aqueous solutions. We examined how the initial metal concentration, flow rate, and bed height affected the adsorption characteristics. Experimental results confirmed that the adsorption capacity increased with increase in influent metal concentration and bed height and decreased with increase in flow rate. The breakthrough and the column kinetic parameters were successfully predicted with three mathematical models: Thomas, Yoon-Nelson, and Adams-Bohart models. Both Thomas and Yoon-Nelson models showed good agreement with the experimental results for all the operating conditions. Successful desorption of heavy metals from the P(St-DVB)/CuNi BNC was performed using 0.5 M NaOH solution, and it showed good reusability of the adsorbent during four adsorption-desorption cycles. The results show that P(St-DVB)/CuNi BNC are effective and low-cost adsorbents, and they can be used in real-time large-scale industrial water treatment processes for the removal of heavy metals